2010
DOI: 10.1111/j.1365-2125.2010.03772.x
|View full text |Cite
|
Sign up to set email alerts
|

Repaglinide‐gemfibrozil drug interaction: inhibition of repaglinide glucuronidation as a potential additional contributing mechanism

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Co-administration of gemfibrozil significantly increases the exposure of repaglinide.• CYP3A4 and CYP2C8 are important in the metabolism of repaglinide.• OATP1B1 polymorphism is an independent predictor of repaglinide pharmacokinetics.• Gemfibrozil and its O-glucuronide are CYP2C8 and OATP1B1 inhibitors. WHAT THIS STUDY ADDS• Acyl glucuronidation is a major metabolic pathway of repaglinide in vitro.• Gemfibrozil and its glucuronide inhibit the glucuronidation of repagl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…Antidiabetic Agents. The nonsulfonylurea insulin secretagogue repaglinide is metabolized primarily by CYP2C8 (Table 4) and CYP3A4, but it also undergoes direct glucuronidation by uridine-59-diphosphoglucuronosyltransferase (UGT) 1A1 (Bidstrup et al, 2003;Kajosaari et al, 2005a,b;Gan et al, 2010). In addition, there is in vitro data suggesting that aldehyde dehydrogenase is involved in its metabolism (Säll et al, 2012).…”
Section: A Drugsmentioning
confidence: 99%
“…Antidiabetic Agents. The nonsulfonylurea insulin secretagogue repaglinide is metabolized primarily by CYP2C8 (Table 4) and CYP3A4, but it also undergoes direct glucuronidation by uridine-59-diphosphoglucuronosyltransferase (UGT) 1A1 (Bidstrup et al, 2003;Kajosaari et al, 2005a,b;Gan et al, 2010). In addition, there is in vitro data suggesting that aldehyde dehydrogenase is involved in its metabolism (Säll et al, 2012).…”
Section: A Drugsmentioning
confidence: 99%
“…The authors estimated CYP2C8 to account for ;80% of montelukast metabolism in humans (Karonen et al, 2010(Karonen et al, , 2012 and recommended montelukast as a selective CYP2C8 probe of activity in vivo. However, gemfibrozil inhibits multiple drug disposition proteins other than CYP2C8 to varying degree (Wen et al, 2001;Prueksaritanont et al, 2002;Shitara et al, 2004;Noe et al, 2007;Mougey et al, 2009;Gan et al, 2010), and it is possible the observed in vivo effect of gemfibrozil may have been mediated in part through inhibition of other pathways in addition to the known inhibition of CYP2C8. Consistent with a previous study showing inhibition of expressed UGT1A3 by gemfibrozil (Gan et al, 2010), our in vitro data show modest inhibition of montelukast glucuronidation in HLMs, although the potency of this inhibition appears too low to explain the effect of gemfibrozil on montelukast exposure in vivo.…”
Section: Downloaded Frommentioning
confidence: 99%
“…When rifamycin SV was present to inhibit active uptake clearance ( Fig. 1), an inhibited metabolic clearance (F inhibition  CL int, u, met ) was used to represent potential inhibition of glucuronidation by rifamycin SV observed in the current study and a previous study (Gan et al, 2010): …”
Section: Downloaded Frommentioning
confidence: 99%